Supporting Factors and Consequences of Child Marriage - Nilla S. D. Iustitiani; Clara R. P. Ajisuksmo (ANIMA Indonesian Psychological Journal, 2018)
This study aims to give an overview of the causes and consequences of child marriage by qualitative research using in-depth interview techniques. Participants were eight girls who married during their childhood and live in Java, Indonesia. Interviews were analyzed by using content analysis techniques. The results show that underlying factors causing child marriage, include the following: (1) unwanted pregnancy; (2) the influence of parents and the surrounding environment for fear of slander and unwanted things; (3) education; and (4) economy. The consequences of child marriage include: (1) dicontinuation of education; (2) economic instability; (3) violation of law, age falsification, unregistered marriage, difficulties in obtaining birth certificates; (4) deprivation of children's liberty and autonomy; (5) psychological problems; (6) violence; and (7) health problems especially in girls.